Antenatally detected multiple mediastinal enterogenous cysts in a newborn presenting with severe cardio-respiratory compromise and early life-saving management - Abhijit Modak; Shashi Kant Dhir; Adil Ahmed Khan; Pulkit Rastogi; Nitin James Peters; Kanya Mukhopadhyay (Wolters Kluwer Medknow Publications, 2021)
Posterior mediastinal enterogenous cyst is a rare entity in neonate. The neonate can present with severe cardio-respiratory compromise in the form of respiratory distress, shock, cardiac failure or arrhythmia soon after birth which may require immediate surgical intervention. Antenatal screening can demonstrate the cystic mass in fetus early and can help in quick postnatal management. Multidisciplinary management with aspiration of the cysts was life-saving in the present case.